2018
DOI: 10.1007/s10295-018-2031-7
|View full text |Cite
|
Sign up to set email alerts
|

Redox cofactor engineering in industrial microorganisms: strategies, recent applications and future directions

Abstract: NAD and NADP, a pivotal class of cofactors, which function as essential electron donors or acceptors in all biological organisms, drive considerable catabolic and anabolic reactions. Furthermore, they play critical roles in maintaining intracellular redox homeostasis. However, many metabolic engineering efforts in industrial microorganisms towards modification or introduction of metabolic pathways, especially those involving consumption, generation or transformation of NAD/NADP, often induce fluctuations in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 147 publications
0
41
0
Order By: Relevance
“…We speculated that the problematic imbalance of NADH/NAD + ratio might be a limiting factor that restricted further improvement of l ‐threonine production. One possible strategy for resolving this issue was to introduce an extra NADH regeneration pathway (J. Liu, Li, Zhao, Caiyin, & Qiao, ). NAD + ‐dependent FDH, catalyzing formate oxidation with conversion of NAD + to NADH, has been widely used for to increase NADH availability in metabolic engineering due to its proven effectiveness and innocuous product (carbon dioxide; Balzer, Thakker, Bennett, & San, ; H. S. Song et al, ; M. Wang, Wang, Zhang, Fan, & Tan, ).…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that the problematic imbalance of NADH/NAD + ratio might be a limiting factor that restricted further improvement of l ‐threonine production. One possible strategy for resolving this issue was to introduce an extra NADH regeneration pathway (J. Liu, Li, Zhao, Caiyin, & Qiao, ). NAD + ‐dependent FDH, catalyzing formate oxidation with conversion of NAD + to NADH, has been widely used for to increase NADH availability in metabolic engineering due to its proven effectiveness and innocuous product (carbon dioxide; Balzer, Thakker, Bennett, & San, ; H. S. Song et al, ; M. Wang, Wang, Zhang, Fan, & Tan, ).…”
Section: Resultsmentioning
confidence: 99%
“…Traditional UV mutagenesis is a mature technique that induces a high mutation rate into the receptor strains. Engineering the ribo avin biosynthesis by increasing the supplement of the precursor to the avin coenzyme formation is an e cient pathway that could indirectly activate the secondary metabolite biosynthesis [38][39][40][41]. This cofactor engineering type method has been well utilized in another marine actinomycete [44].…”
Section: Discussionmentioning
confidence: 99%
“…Further enhancement of CRM A production by optimizing intracellular ribo avin supplement Enhancing the cofactor level by engineering its biosynthetic process could drive metabolic ux to improve the biosynthesis of target metabolites [38]. This new metabolic engineering strategy named as cofactor engineering has been well applied to microbial second metabolites development [39][40][41]. Previous study had revealed that the biosynthesis of CRM A required several essential avoenzymes, including CamD, which completed the formation of the picolinic acid precursor; CamH, which catalyzed the formation of the oxime group, and CamK, which maintained the substrate recycling process [23,28,29].…”
Section: Enhancement Of Crm a Production By Uv Mutagenesismentioning
confidence: 99%
“…In order to further increase the production of 3β-O-Glc-DM and 20S-O-Glc-DM, the cofactor engineering strategies can be used for solving the problematic redox imbalance in metabolic modification in the future. 41,42 Production of 3β-O-Glc-DM and 20S-O-Glc-DM through fed-batch fermentation In order to achieve higher production of 3β-O-Glc-DM and 20S-O-Glc-DM, we chose the engineered strains Y1CSH and Y2CSH for fed-batch fermentation which was performed in a 3 L bioreactor with the pH controlled at 5.5. As shown in Fig.…”
Section: Effect Of Overexpressing Of Chaperone and Transcriptional Acmentioning
confidence: 99%